(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Cu2ZnSnSe4 thin films were obtained by sequential deposition of basic elements (Sn, Se, Zn, Cu) on a glass substrate. The thickness of each layer was selected to achieve 2:1:1:4 stoichiometric ratio for copper, zinc, tin and selenium, respectively. To obtain compound Cu2ZnSnSe4 samples were annealed at temperature range of 1500C to 4000C. Surface of samples were investigated using scanning electron microscope. Analysis of chemical composition and x-ray diffractometry was performed before and after annealing of samples.